Modeling of economic assessment of intellectual potential at machine-building enterprises of Ukraine - Marchuk, L. S. (Wyższa Szkoła Finansów i Prawa w Bielsku-Białej, Polska, 2020)
The article conducts an economic assessment of intellectual potential, which has a significant impact on its development. The main purpose: research of structure of branch of mechanical engineering of Ukraine. The practice of realization of forms, processes and principles of production activity of machine-building branch is studied and presented. The role of labor resources in the intellectual and innovative development of mechanical engineering as a major factor in the effectiveness of intellectual potential and the national economy in general. Particular attention is paid to the state as a decisive factor in the development of mechanical engineering, because there is a need to create decent conditions for the state to successfully master the economic, managerial, technological, production, intellectual and innovative factors of mechanical engineering. Formulation of the problem – the machine-building industry plays a leading role in the industry of Ukraine. The development of machine-building enterprises depends on a number of factors, the formation of which includes elements of production activity, which necessitates an economic assessment of intellectual potential. After all, with the help of economic evaluation is an analysis of the development and effectiveness of the intellectual potential of the industrial enterprise. Such circumstances, in turn, require the creation of sound scientific and methodological approaches to the assessment, formation, use and development of intellectual potential